Encyclopedia of Life Sciences 2014
DOI: 10.1002/9780470015902.a0020711.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Plant Virus Movement

Abstract: Plant virus movement is the process of the spread of virus genetic material from the initially infected cells to the rest of the plant. There are several distinct stages including intracellular movement from sites of virus replication to plasmodesmata (PD) (plant‐specific intercellular nanopores), cell‐to‐cell trafficking through PD and long‐distance movement between organs through the phloem (the specialized vascular system used by plants for the transport of assimilates and macromolecules). Transport is medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Studies of plant virus cell-to-cell movement carried out in the last 35 years have revealed several types of viral transport system exhibiting remarkable differences in their gene organization, as well as in the structure and biochemical properties of their encoded movement proteins (MPs), with the movement functions being performed by a single protein or distributed among several MPs (Heinlein, 2015;Lucas, 2006;Tilsner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of plant virus cell-to-cell movement carried out in the last 35 years have revealed several types of viral transport system exhibiting remarkable differences in their gene organization, as well as in the structure and biochemical properties of their encoded movement proteins (MPs), with the movement functions being performed by a single protein or distributed among several MPs (Heinlein, 2015;Lucas, 2006;Tilsner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Successful infection of a plant host by a virus derives from its ability to spread from the initial infection site to distant tissues and organs. This process involves various steps in different cellular compartments: intracellularly from the replication site to the cell periphery, through the cell wall to the adjacent cell, across tissues to the vascular system (usually phloem sieve tubes) and through the conductive elements to distant host tissues, where the virus can initiate systemic infection (Harries and Nelson, 2008;Hull, 2014;Schoelz et al, 2011;Tilsner et al, 2014;Ueki and Citovsky, 2007). In all the intercellular stages, viruses must traverse a substantial barrier that surrounds the host cells: the plant cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins 155 were chosen to represent common types of virus movement proteins (Tilsner et al, 2014; …”
mentioning
confidence: 99%